Papua New Guinea High Frequency Phone Survey on COVID-19, December 2020 to January 2021 - World Bank; UNICEF (World Bank, Washington, DC, 2021)
This joint report by the World Bank and United Nations International Children’s Emergency Fund (UNICEF) Papua New Guinea (PNG) presents the findings from two mobile phone surveys conducted in December 2020 and January 2021 in PNG. The World Bank survey, conducted in December 2020, was the second in a series. The UNICEF survey, conducted in January 2021, targeted re-contacting all 2,534 households from the World Bank round 2 survey with children under the age of 15, and achieved a final sample of 2,449. These results were also weighted using information from the demographic and health survey (DHS) to develop representative estimates for households with children under 15, 79.8 percent according to the DHS. The UNICEF survey included sections on household impacts as well as on the children living within the household. Compared to the rest of the country, markedly higher shares of respondents in the NCD noted deteriorations since June in situations related to theft, alcohol, and drug abuse, intimidation by police, violence by police, and domestic abuse, as well as higher declines in overall community trust, which can be an indicator of rising tensions. In addition, there were potential warning signs of the impacts of the prolonged crisis on children, with more than one-third of children exhibiting negative behavioral changes in the previous 15 days - though again a lack of baseline data limits the ability to establish a causal link specifically with Coronavirus disease 2019 (COVID-19).